Pengaruh konseling gizi dengan buku saku diet pada pasien hiperurisemia rawat jalan di RSUD Noongan Provinsi Sulawesi Utara - Maxie Roudy Reppie; Ahmad Husain Asdie; Herni Astuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2007)
Background: The prevalence of hyperuricemia in Minahasa was quite high in Indonesia. This is caused by nutrition/food intake and life style factors. These changes can be handled with nutrition counseling activity in order to change attitude and food behavior by using nutrition counseling equipment that is diet pocket book.Objective: In order to find out the influence of nutrition counseling with diet pocket book toward the control of purine intake and blood uric acid level in hyperuricemia patients who experienced outpatient treatment in Noongan district hospital.Method: This was a quasi-experimental research that used pre and posttest control group design. The subject of the research was hyperuricemia patients who experienced outpatient treatment in Noongan district hospital. The subject was divided into two groups: intervention group (n=28 people) which was given nutrition counseling with diet pocket book and control group (n=28 people) which was given nutrition counseling without diet pocket book. The sample was taken purposively.Result: The decreasing average of uric acid in the beginning and end of the research was 1.62 mg/dL in intervention group and 0.85 mg/dL in control group. There was a significant difference on the decreasing average of blood uric acid between respondent in intervention group and in control group. The result of statistical analysis with t-test showed that p=0.000. The purine intake in the beginning of the research was p=0.105 with insignificant different while the purine intake at the end of the research which was p=0.009 also showed insignificant different. If the comparison was the decreasing average of purine intake in the beginning and end of the re-search, there was a decreasing of purine intake in intervention group of 53.78 while in control group was 35.39. The statistical analysis of p=0.000 showed that there was a significant different on the average of purine intake decreasing between respondent of intervention group with respondent of control group. In the high purine of food ingredient in-take, there was an insignificant different of high purine intake decreasing between intervention group and control group with p=1.38. On the other hand, in the intake of medium purine food ingredient showed significant different in the decreasing of purine food intake in the intervention group and control group with p=0.000.Conclusion: The control of blood uric acid level and control of purine intake of hyperuricemia patients who were given nutrition counseling with diet pocket book was better than nutrition counseling without diet pocket book.